Autoantibody of NRIP, a novel AChR‐interacting protein, plays a detrimental role in myasthenia gravis. Issue 3 (26th March 2021) - Tsai, Li‐Kai; Chen, I‐Hsin; Chao, Chi‐Chao; Hsueh, Hsueh‐Wen; Chen, Hsin‐Hsiung; Huang, Yun‐Hsin; Weng, Rong‐Wei; Lai, Tzu‐Yun; Tsai, Yi‐Chieh; Tsao, Yeou‐Ping; Chen, Show‐Li
Abstract: Background: Nuclear receptor interaction protein (NRIP) co‐localizes with acetylcholine receptor (AChR) at the neuromuscular junction (NMJ), and NRIP deficiency causes aberrant NMJ architecture. However, the normal physiological and pathophysiological roles of NRIP in NMJ are still unclear. Methods: We investigated the co‐localization and interaction of NRIP with AChR‐associated proteins using immunofluorescence and immunoprecipitation assay, respectively. The binding affinity of AChR‐associated proteins was analysed in muscle‐restricted NRIP knockout mice and NRIP knockout muscle cells (C2C12). We further collected the sera from 43 patients with myasthenia gravis (MG), an NMJ disorder. The existence and features of anti‐NRIP autoantibody in sera were studied using Western blot and epitope mapping. Results: NRIP co‐localized with AChR, rapsyn and α‐actinin 2 (ACTN2) in gastrocnemius muscles of mice; and α‐bungarotoxin (BTX) pull‐down assay revealed NRIP with rapsyn and ACTN2 in complexes from muscle tissues and cells. NRIP directly binds with α subunit of AChR (AChRα) in vitro and in vivo to affect the binding affinity of AChR with rapsyn and rapsyn with ACTN2. In 43 patients with MG (age, 58.4 ± 14.5 years; female, 55.8%), we detected six of them (14.0%) having anti‐NRIP autoantibody. The presence of anti‐NRIP autoantibody correlated with a more severe type of MG when AChR autoantibody existed ( P = 0.011). The higher the titre of anti‐NRIP autoantibody, the more severe MG severity ( P = 0.032). The main immunogenic region is likely on the IQ motif of NRIP. We also showed the IgG subclass of anti‐NRIP autoantibody mainly to be IgG1. Conclusions: NRIP is a novel AChRα binding protein and involves structural NMJ formation, which acts as a scaffold to stabilize AChR–rapsyn–ACTN2 complexes. Anti‐NRIP autoantibody is a novel autoantibody in MG and plays a detrimental role in MG with the coexistence of anti‐AChR autoantibody.